Quantifying Biochemical Alterations in Brown and Subcutaneous White Adipose Tissues of Mice Using Fourier Transform Infrared Widefield Imaging - Aboualizadeh, Ebrahim; Carmichael, Owen T.; He, Ping; Albarado, Diana C.; Morrison, Christopher D.; Hirschmugl, Carol J. (Frontiers in Endocrinology, 2017)
Stimulating increased thermogenic activity in adipose tissue is an important biological target for obesity treatment, and label-free imaging techniques with the potential to quantify stimulation-associated biochemical changes to the adipose tissue are highly sought after. In this study, we used spatially resolved Fourier transform infrared (FTIR) imaging to quantify biochemical changes caused by cold exposure in the brown and subcutaneous white adipose tissues (BAT and s-WAT) of 6 week-old C57BL6 mice exposed to 30°C (N=5), 24°C (N=5), and 10°C (N=5) conditions for 10 days. Fat exposed to colder temperatures demonstrated greater thermogenic activity as indicated by increased mRNA expression levels of a panel of thermogenic marker genes including UCP-1 and Dio2. Protein to lipid ratio, calculated from the ratio of the integrated area from 1600-1700 cm-1 (amide I) to the integrated area from 2830-2980 cm-1 (saturated lipids), was elevated in 10°C BAT and s-WAT compared to 24°C (p = 0.004 and p < 0.0001) and 30°C (p = 0.0033 and p < 0.0001). Greater protein to lipid ratio was associated with greater UCP1 expression level in the BAT (p = 0.021) and s-WAT (p = 0.032), and greater Dio2 expression in s-WAT (p = 0.033). The degree of unsaturation, calculated from the ratio of the integrated area from 2992-3020 cm-1 (unsaturated lipids) to the integrated area from 2830-2980 cm-1 (saturated lipids), showed intuitive stepwise decreases going from colder-exposed to warmer-exposed BAT. Complementary 1H NMR measurements confirmed the findings from this ratio in BAT. Principal Component Analysis (PCA) applied to FTIR spectra revealed pronounced differences in overall spectral characteristics between 30°C, 24°C, and 10°C BAT and s-WAT. Spatially-resolved FTIR imaging is a promising technique to quantify cold-induced biochemical changes in BAT and s-WAT in a label-free manner.